Experiences with COVID-19 Among Gig Workers - Salter L; Dutta M (Massey University, 2022)
Currently, little is known about the experiences of gig workers in Aotearoa New Zealand, including the nature and quality of their day-to-day work, or how they have negotiated the disruption and risk brought to bear by the COVID-19 pandemic. Largely erased from the conceptual frameworks examining gig work are the voices of workers. This white paper takes a Culture-Centered Approach (CCA) to gig work, seeking to co-create voice infrastructures in partnership with gig workers, attending to the classed, raced, gendered nature of gig work, and the ways in which the structural characteristics of gig work which ingrain precarity are exacerbated by the pandemic. Drawing on 25 in-depth interviews with participants who are currently or have recently worked as rideshare or food delivery gig workers, this report argues that platformed work - organised and mediated through an online platform or app, is structurally distinct from traditional forms of work.